A Case Report of Unilateral Pediatric Cataract Surgery: Posterior Capsule Opacification and Visual Rehabilitation - Dian Estu Yulia; Ferdinand Inno Luminta (Majalah Oftalmologi Indonesia, 2021)
Objective: To report a case of posterior capsule opacification (PCO) and severe deprivation amblyopia following unilateral pediatric cataract surgery Case Presentation: A 4-year-old girl presented with PCO of the right eye with a history of unilateral congenital cataract surgery and intraocular lens (IOL) implantation without optimal visual rehabilitation two years ago at another hospital in Jakarta. Her uncorrected right eye visual acuity was 3/60 and corrected left eye visual acuity 6/7.5. We performed secondary posterior capsulotomy and anterior vitrectomy of the right eye. Following the procedure, the patient did not regain her vision despite normal posterior segment; thus, a diagnosis of deprivation amblyopia was made. She was prescribed occlusion therapy for 6 hours a day on the left eye to decrease the degree of amblyopia of her right eye. Conclusion: Early identification and management of pediatric cataract surgery complications combined with optimal visual rehabilitation may benefit the patient in the long run. If not treated properly, especially in unilateral cataract cases, it may be too late to regain visual function.